2015
DOI: 10.1007/s00710-015-0367-5
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformation of Mg-calcite to aragonite in active-forming hot spring travertines

Abstract: A travertine specimen collected from the western part of Yunnan Province of China was subjected to microstructural analysis by powder X-ray diffraction, scanning electron microscopy, high resolution transmission electron microscopy and energy dispersive X-ray spectroscopy. A new formation mechanism was proposed whereby polycrystalline rhombohedral particles of magnesium-containing calcite underwent a phase transformation into sheaf-like clusters of aragonite microrods. It is proposed that a high concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…38 In this work, aragonite formation was not detected at any stage of the crystallization process because the experiments were done in big droplets, at room temperature and without any aragonitepromoting additive such as magnesium ions. This is consistent with the literature, where at room temperature aragonite formation has been observed to occur either in connement $25 nm pores 39,40 or in solutions containing inorganic additives such as magnesium ions [41][42][43][44][45][46][47][48] or organic additives/solvents. [49][50][51] Carbon dioxide has a strong inuence on the pH of aqueous solutions because it readily dissolves in water to form carbonic acid, which dissociates to bicarbonate and carbonate ions respectively (eqn (1)).…”
Section: In Situ Study Of Calcium Carbonate Crystallization From Solusupporting
confidence: 92%
“…38 In this work, aragonite formation was not detected at any stage of the crystallization process because the experiments were done in big droplets, at room temperature and without any aragonitepromoting additive such as magnesium ions. This is consistent with the literature, where at room temperature aragonite formation has been observed to occur either in connement $25 nm pores 39,40 or in solutions containing inorganic additives such as magnesium ions [41][42][43][44][45][46][47][48] or organic additives/solvents. [49][50][51] Carbon dioxide has a strong inuence on the pH of aqueous solutions because it readily dissolves in water to form carbonic acid, which dissociates to bicarbonate and carbonate ions respectively (eqn (1)).…”
Section: In Situ Study Of Calcium Carbonate Crystallization From Solusupporting
confidence: 92%
“…No phase transformation occurred even when the hydrothermal time was extended to 5 days in our system, unlike the phase transformation from magnesium calcite to aragonite in a travertine crust specimen. 44 We propose that the hydrothermal process at 150 °C for 24 hours is appropriate for the synthesis of well crystallized high Mg calcites in this work. The hydrothermal process for the synthesis of high Mg calcites ]/[Ca 2+ ] and [Mg 2+ ]/[Ca 2+ ] were changed in this work.…”
Section: mentioning
confidence: 99%
“…3.1. Morphology: In the process of experiment, we found that different preparation methods, even a small change in the type and amount of additives or a slight change in reaction conditions would cause a huge change in crystal morphology and particle shape [30][31][32][33].…”
Section: Resultsmentioning
confidence: 99%